Ecclesial spirituality in the Korean Presbyterian Church : a practical and hermeneutical investigation into the problem of marginality - Kim, Soon-Seong (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2004